Two-Stem Anthroponyms in Name List of Texts of 15th-17th Centuries - I. A. Kyurshunova (Научный диалог)
The relevance of the study is determined by the rare appeal of onomatologists to studying two-stems anthroponomical units, which in turn is due to their low quantitative representation in the texts of the mass census and act materials of the epochs before national period. The written sources of a peripheral region of Russia - the Republic of Karelia of 15th-17th centuries - are chosen for the analysis. By the continuous sampling the names are extracted out of these texts and divided into two groups: composites (for example, Yaroslav ) and two-stem nicknames (for example, Batonogiy ). They are marked by their social and genetic heterogeneity. Semantic and motivational features of words, cultural and historical information within them, anthropocentric potential are characterized. It is shown that after the baptism of Rus the representatives of the peasant society were named by the ancient princely names-composites. Composite names, remaining in the circle of non-calendar personal names, subject to various structural changes. It is assumed that the motive of naming could have high politely meaning inherent in the mythological consciousness of the pre-Christian society, and a set of elements distinguished Slavic composites from Indo-European names of this kind, as well as from the Russian two-stem nicknames, the main function of which was the explicit characterization of the physical data and (rarely) the inner qualities of a person.